Reliability of health-related quality-of-life assessments made by older adults and significant others for health states of increasing cognitive impairment. Issue 1 (January 2017) - Bravo, Gina; Sene, Modou; Arcand, Marcel
Abstract Background Older adults are encouraged by many organizations to engage in advance care planning in the event of decisional incapacity. Planning for future health care often involves anticipating health-related quality of life (HRQoL) in states of reduced cognitive functioning. No study has yet examined whether anticipated HRQoL is stable over time. The accuracy with which significant others can predict how an older adult envisions HRQoL in a future state of cognitive impairment is also unknown. We investigated the extent to which health-related quality-of-life ratings made by older adults and designated proxies for health states of increasing cognitive impairment are consistent over time and agree with each other. Methods Results are based on HRQoL ratings made on a 5-point Likert scale by 235 community-based elder-proxy dyads on three occasions. Ratings were obtained for the older adult's current health state as well as under the assumption that he/she had a mild to moderate stroke, incurable brain cancer or severe dementia. Data were analyzed using both traditional approaches (e.g., intraclass correlation coefficients, Bland-Altman plots) and the theory of generalizability. Results We found ratings to be reasonably consistent over time and in good agreement within dyads, even more so as implied cognitive functioning worsened. Across health states, ratings over time or within elder-proxy dyads were no more than one category apart in over 87% of cases. Using the theory of generalizability, we further found that, of the two facets investigated, rater had a greater influence on score variability than occasion. Conclusions These findings underscore the importance of discussing health-related quality-of-life issues during advance care planning and involving designated proxies in the discussion to enhance their understanding of the role that HRQoL should play in actual decision-making situations. Medical decision-making may be influenced by healthcare providers' and family members' assessments of an incapacitated patient's health-related quality of life, in addition to that of the designated proxy. Future studies should investigate whether these two groups of individuals share the views of the patient and the designated proxy on anticipated HRQoL.